2022
DOI: 10.1002/pc.26707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fumed silica and halloysite nanoparticles on the microstructure, mechanical, and fracture properties of thermoplastic polyolefin elastomer toughened polypropylene

Abstract: In this article, mechanical and fracture properties of two types of nanoparticles, namely fumed silica (FS) and halloysite nanotube filled polypropylene (PP) toughened with two types of thermoplastic elastomers (TPOs), namely ethylene-based TPO (ETPO) and propylene-based TPO (PTPO) were investigated. A full factorial design was exploited to clarify the influence of each factor as well as its interaction on outcomes. The essential work of fracture (EWF) approach was utilized to study the effect of each factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 76 publications
(125 reference statements)
0
27
0
Order By: Relevance
“…The specific terms of the essential work of fracture are obtained after dividing equation (2) by the cross-sectional area of the ligament lengthwhere w e and βw p are specific essential work of fracture and specific non-essential work of fracture, in turn. 36 The total work of fracture (w f ) is calculated by integrating the area under the force-displacement diagram. According to equation (3), there is a linear function between w f and the ligament length.…”
Section: The Theory Of Ewfmentioning
confidence: 99%
“…The specific terms of the essential work of fracture are obtained after dividing equation (2) by the cross-sectional area of the ligament lengthwhere w e and βw p are specific essential work of fracture and specific non-essential work of fracture, in turn. 36 The total work of fracture (w f ) is calculated by integrating the area under the force-displacement diagram. According to equation (3), there is a linear function between w f and the ligament length.…”
Section: The Theory Of Ewfmentioning
confidence: 99%
“…[4,5] However, the performance of PP as an engineering material is limited by its poor toughness, which is a key factor for practical applications of PP, especially at low temperatures or high strain rates. [4,6,7] In recent years, various techniques have been used to improve the fracture toughness of PP. Among different techniques for toughness modification, the addition of elastomers and nanoparticles has received great attention.…”
Section: Introductionmentioning
confidence: 99%
“…Among different techniques for toughness modification, the addition of elastomers and nanoparticles has received great attention. [6][7][8][9][10] Elastomer toughening modification is considered a common method for improving the PP toughness. In this method, several factors, including microstructure, size and number of particles, and interfacial interactions between the rubber and polymer matrix play a significant role in the efficiency of toughening enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] So far, there are many reports using this approach for nanocomposites manufacturing and investigation of mechanical, thermal, and fracture mechanisms of these materials. [7,8] For example, studies by Paran et al [9] on fracture behavior of PA6/NBRXNBR-grafted HNTs nanocomposites showed that the essential work of fracture parameter increased with the incorporation of XNBR-grafted into the matrix. In contrast, the nonessential work of fracture parameter decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of curing systems and NBR/PA6 ratio on thermal properties and morphology of NBR/PA6 blends were investigated by Mehrabzadeh et al [ 13 ] They showed that the phenolic curing system for NBR/PA6 (60/40) matrix has the most significant influence on improving the thermal and mechanical properties. Haghnegahdar et al [ 8 ] have investigated the effect of the type of graphene and curing system on the failure mechanism of PP/EPDM/graphene nanocomposite. They reported that the type of graphene played a different role in the fracture toughness mechanism.…”
Section: Introductionmentioning
confidence: 99%